How Does Employment Protection Legislation Affect Unemployment in Tunisia? : A Search Equilibrium Approach - Fanizza, Domenico (IMF Working Papers; Working Paper, 2005)
This paper applies a search matching model with firing restrictions to examine whether the existence of firing restrictions affects the outcome of the matching process and the natural rate of unemployment in Tunisia. The paper concludes that the removal of firing restrictions is likely to produce a favorable but limited impact on unemployment in Tunisia.